Activation of bovine neutrophils by partially purified Pasteurella haemolytica leukotoxin. - Czuprynski, C J (Infect Immun, 1991)
In this study we developed a new method for the partial purification of Pasteurella haemolytica leukotoxin by size-exclusion high-performance liquid chromatography. The partially purified leukotoxin had a molecular weight of 104,000, as estimated by using sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and reacted on an immunoblot with an antileukotoxin monoclonal antibody. As expected, high concentrations of the leukotoxin were inhibitory or lethal to bovine neutrophils. Incubation of bovine neutrophils with diluted leukotoxin, however, resulted in significant neutrophil activation that was comparable in magnitude to that obtained with standard activating agents such as opsonized zymosan or zymosan-activated serum. Dilute leukotoxin (1:128 to 1:8,192 dilutions) stimulated an oxidative burst (luminol-dependent chemiluminescence) by bovine neutrophils that was comparable in magnitude to that obtained with opsonized zymosan. Preincubation with leukotoxin did not significantly prime the neutrophils for an enhanced oxidative burst when they were then exposed to opsonized zymosan as a second stimulus. Dilute leukotoxin (1:100 to 1:1,000 dilutions) also stimulated cytoskeletal alterations in bovine neutrophils, as measured by a significant shape change response. Preferential release of secondary granule constituents (lactoferrin) occurred when neutrophils were incubated with 1:100 to 1:500 dilutions of leukotoxin. Significant release of primary granules, as measured by beta-glucosaminidase activity, was not observed except at low dilutions (1:20) of leukotoxin that resulted in significant release of cytosolic constituents (i.e., lactate dehydrogenase activity). The neutrophil-activating activity of the leukotoxin was heat labile, unaffected by polymyxin B, and abrogated by a leukotoxin-neutralizing monoclonal antibody. These data indicate that P. haemolytica leukotoxin, like the closely related Escherichia coli hemolysin, is a potent neutrophil-activating agent. Leukotoxin-stimulated release of neutrophil oxygen intermediates and granule constituents may contribute to the intense inflammation that characterizes bovine pulmonary pasteurellosis. IMAGES: